Is valve-sparing aortic root replacement better than total aortic root replacement? An overview of reviews - Wang, Wei; Zhang, Xuezhou; Shi, Yong; Xu, Siqi; Shi, Teng; Han, Xiaotian; Gu, Tianxiang; Shi, Enyi (Frontiers in Cardiovascular Medicine, 2023)
Background Total aortic root replacement (TRR) is certainly beneficial for aortic root disease, but does it still have an advantageous prognosis for patients compared to valve-sparing aortic root replacement (VSRR)? An overview of reviews was conducted to assess each of their clinical efficacy/effectiveness. Review methods Systematic reviews (SRs)/Meta-analyses comparing the prognosis of TRR and VSRR in aortic root surgery were collected from 4 databases, all searched from the time of database creation to October 2022. Two evaluators independently screened the literature, extracted information and applied the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR 2) tool, Grading of Recommendations, Assessment, Development and Evaluations (GRADE), and Risk of Bias in Systematic Reviews (ROBIS) to evaluate the quality of reporting, methodological quality, risk of bias, and level of evidence of the included studies. Main results A total of 9 SRs/Meta-analyses were ultimately included. In terms of the reporting quality of the included studies, PRISMA scores ranged from 14 to 22.5, with issues mainly in reporting bias assessment, risk of study bias, credibility of evidence, protocol and registration, and funding sources. The methodological quality of the included SRs/Meta-analyses was generally low, with key items 2, 7, and 13 having major flaws and non-key items 10, 12, and 16. In terms of risk of bias assessment, the overall assessment of the included 9 studies was high-risk. The quality of the evidence was rated as low to very low quality for the three outcome indicators selected for the GRADE quality of evidence rating: early (within 30 days postoperatively or during hospitalization) mortality, late mortality, and valve reintervention rate. Conclusions VSRR has many benefits including reduced early and late mortality after aortic root surgery and reduced rates of valve-related adverse events, but the methodological quality of the relevant studies is low, and there is a lack of high-quality evidence to support this. Systematic Review Registration https://www.PROSPERO, identifier: CRD42022381330.